Diversified Approach to Quantification of Risks that Arise in Projects Associated with Extraction of Hydrocarbon Resources in the Arctic - DUDIN, Mihail Nikolaevich; LYASNIKOV, Nikolay Vasilievich; KATUL'SKIY, Evgeniy Danilovich; SHHIPANOVA, Dorina Grigor'evna; CHEKANOV, Andrey Evgen'evich (Journal of Environmental Management and Tourism; Vol 8 No 1 (2017): JEMT Volume VIII Issue 1(17) Spring 2017DO - 10.14505//jemt.v8.1(17).03, 2017)
Intensification of oil and gas extraction in the Arctic and a consequent growth of the volume of transported oil increase the likelihood of occurrence of various risk events. The companies engaged in extraction of hydrocarbons in the Arctic territory face the need to assess numerous risks. Quantification of information about risks is determined by the need to obtain numerical data that would allow carrying out a prospective economic analysis of exploration activities in the Arctic territory. The article presents a method of quantification of risks, the use of which allows translating the linguistic characteristic of any harmful event into measured categories. This method found its actual use in the assessment of three groups of risk ("asset security risks", "environmental risks" and "reliability risks") associated with the companies’ production activity on extraction of hydrocarbons in the Arctic. The following conclusions were obtained following the results of presentation of the materials in the article: hydrocarbon reserves in the Arctic shelf determine the growth of corporate and state interests in their commercial development. However, extraction of hydrocarbon resources in the Arctic at the same time a priori carries a high level of risks associated with the climatic features of the region, the fragility of its ecosystem, and the need to develop and consequently use special equipment and technology; as a rule, Russian companies that implement Arctic projects assess the risks of these projects linguistically and empirically, without conducting their quantitative or monetary estimate. This is why the problem of quantification of risks of Arctic projects is the most urgent today and requires the development of new methodological approaches; this article presents and partially tests the method of quantification of risks of Arctic projects by the example of the Novoportovskoye field and extraction of hydrocarbons using the offshore ice-resistant fixed platform "Prirazlomnaya". The assessment findings show that the risks of these projects do not exceed average values; publication of quantified information about risks of ongoing Arctic projects in the official reports of the Russian companies will ensure the transparency of their operations and increase the level of their social and environmental responsibility to society.